ANALISIS SENSITIVITAS USAHA PENGOLAHAN KERUPUK IKAN PIPIH DI KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN - Lili Winarti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This study aimed to analyze the cost, revenue, profit and the level of sensitivity of flat fish cracker processing business in the district Seruyan Seruyan Hilir. The method used is the method of census, census method is a research method that uses all individuals in the population so that in this study did not use samples. Analysis of the data used is the analysis of qualitative and quantitative analysis, qualitative analysis performed to obtain a picture or descriptive business processing fish cracker flat and quantitative analysis was conducted to analyze the costs incurred for activities ranging from investment costs, operational production to marketing and financial analysis used to find out feasible or not its business of processing flat fish cracker by using the criteria for eligibility of investment are: Net Present Value (NPV), Internal rate of Return (IRR), Net Benefit Cost ratio (Net B / C), Payback Period and analysis sensitivity is used to determine the sensitivity level of effort against the changes to the parameters used in raw material costs rise (10%, 15% and 20%), the selling price of flat fish crackers down (10%, 15% and 20%) and raw material prices rise and the selling price of flat fish crackers down (10%, 15% and 20%). The research results show that the business of processing flat fish cracker cultivated with parameters (10%, 15% and 20%) worth the try and the results of the sensitivity analysis (switching value) indicates that the decrease in production volume or price of fish crackers flattened more sensitive or sensitive when compared to the price increase of raw materials the main manufacture of flat fish crackers.